Items Quality Analysis Using Rasch Model To Measure Elementary School Students’ Critical Thinking Skill On Stem Learning - Ghullam Hamdu; F N Fuadi; A Yulianto; Y S Akhirani (Jurnal Pendidikan Indonesia, 2020)
Critical thinking as one of the 21st century competences required by students needs to be developed and analyzed by employing qualified assessment instrument. Test is a kind of critical thinking assessment instrument which quality is developed and analysed to create a meaningful learning. A total of 10 multiple choices items were developed based on critical thinking indicators. The items were then given to forty two 4th grade students in one of the elementary schools in Tasikmalaya-West Java after obtaining STEM learning. Focus group discussions were conducted to construct and validate the instrument. The result of the test was analyzed using Rasch model with the assistance of Winsteps software version 3.75. The results indicated that the analysis using the Rasch model could explain the critical thinking items’ quality based on the level of difficulty and suitability and could categorize students’ abilities and their suitability for STEM learning conducted.